From Superwoman to Fake Blonde: the representation of blondness on the Brazilian big screen. Issue 1 (2nd January 2016) - Dennison, Stephanie
Abstract : This article examines the various representations of Brazilian blonds on cinema screens, ranging from the 'uber-blonde', strongly associated with Brazil's southernmost states, where large numbers of northern Europeans (Germans, mostly) emigrated in the late nineteenth and early twentieth centuries, to male and female film personas and celebrities who adopt the blond look, either by bleaching their hair or by donning blond wigs. The aim is to reflect on the status afforded blondness in Brazilian culture and the extent to which this status is affected by the characters' gender, racial and social background. While the article will dwell more on screen representations of blond men and women than on 'star texts' in the wider sense of the term, it draws analogies with blond stars and the press and public reaction to them, with a view to reflecting on how blondness and its different manifestations are interpreted in the contemporary Brazilian context.